Anti-IgE therapy for asthma - Menzies-Gow, Andrew (Henry Stewart Talks, 2013)
Anti-IgE therapy for asthma, Allergy can be associated with severe asthma, Omalizumab, a monoclonal anti-IgE, is the first targeted biological therapy for severe asthma with good clinical efficacy, Patient selection, drug administration and length of treatment are discussed